Penyusunan Laporan Keuangan UMKM Berdasarkan Standar Akuntansi Keuangan Entitas Mikro, Kecil dan Menengah (SAK-EMKM) (Study Kasus Di UMKM Bintang Malam Pekalongan) - jilma dewi ayu ningtyas (Politeknik Ganesha Medan, 2017)
Abstract The financial statement of UMKM is very simple and tend to ignore the standard financial administration rules. Ikatan Akuntan Indonesia has prepared SAK-EMKM (Financial Accounting Standards of Micro, Small and Medium Enterprises) which came into effect as of January 1, 2018 to facilitate UMKM in preparing their business financial statements. This study aims to prepare the financial statements of UMKM Bintang Malam based on SAK-EMKM. This research uses descriptive qualitative research method. Sources of data used primary data in the form of interviews and documentation of transaction evidence. The results of the research show the financial statements of the UMKM Bintang Bintang in the form of statements of financial position or balance sheet, income statement and notes on financial statements. Keywords: UMKM Financial Statement, Financial Statement SAK-EMKM.